Effects of N, P, K Nutrition Levels on the Growth, Flowering Attributes and Functional Components in Chrysanthemum morifolium - Kaifang Jiang; Shu Peng; Zimeng Yin; Xiaohui Li; Lei Xie; Meichen Shen; Dahui Li; Junshan Gao (Horticulturae, 2024)
Fertilizer application is a decisive measure for the productivity of medicinal chrysanthemum plants. Therefore, determining the optimal doses of nutrients required for the growth and yield is crucial. In this study, we set out to investigate the effect of various nutrients on the growth, yield, and functional components of chrysanthemum under eight different fertilization levels at seedling, branching, and flowering growth periods. The results show that plant height, stem diameter, and leaf area under the balance fertilization treatment were the highest (82 cm, 0.78 cm, and 38.50 cm2, respectively), while the flower size and yield under the high potassium treatment were significantly increased compared to using balance fertilization. Chlorophyll content was also highest under the high potassium treatment. Moreover, plant defensive antioxidant peroxidase (POD) was responsive to low nitrogen treatment and low phosphorus treatment, while high potassium treatment enhanced the phenylalanine aminolase (PAL) activity and increased the content of flavonoids and chlorogenic acid in Chrysanthemum morifolium. In addition, low phosphorus treatment promoted the accumulation of flavonoids and chlorogenic acid content. Convincingly, the results show that growth, flowering, and functional indicators of chrysanthemum may thrive best under high potassium and balanced fertilization dosages, which will contribute to the development of a new economical chrysanthemum fertilizer ratio.